Teat order affects postweaning behaviour in piglets - Sommavilla,Roberta (2015)
The objective of this study was to investigate if piglets that suck anterior teats differ from the others in the litter in birth weight, if they have higher growth rate during lactation, and if this affects behaviour and post-weaning weight gain, when piglets change to a solid diet. For this, the teat order of 24 litters was determined during suckling. Piglets were weaned on the 28thday of age, and 24 groups were formed, composed of one piglet that sucked on the first two pairs of teats (AT) and three piglets that sucked on the other teats (OT). Even though weight at birth did not vary according to teat order, weight gain at weaning differed between the groups (AT: 6.64, S.E. 0.20kg, OT: 5.73, S.E. 0.13kg; P<0.001). After weaning, AT piglets spent more time lying (P<0.01) and less time eating (P<0.01) and vocalizing (P<0.01), than the other piglets. Other behaviours (agonistic interaction, escape attempt and drinking) did not differ between the groups. Piglets that sucked anterior teats gained more weight until weaning, suggesting they took in more milk; this fact might have lead them to have less contact with solid food before weaning, influencing their post-weaning alimentary behaviour.